2018
DOI: 10.4174/astr.2018.94.2.88
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intradermal absorbable and mattress sutures to close pilonidal sinus wounds with Limberg flap: a prospective randomized comparative study

Abstract: PurposeWe aimed to compare skin closure techniques, standard (intermittent mattress) and continuous subcuticular sutures, following Limberg flap procedure.MethodsFrom July 2013 to July 2015, 92 patients with sacrococcygeal pilonidal disease were prospectively randomized into 2 groups consisting of 46 patients for both. Patients underwent sinus excision and closure with Limberg flap; continuous subcuticular suture was used in subcuticular group (SG) and intermittent mattress sutures were used in mattress group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Using MLF technique, 0.8% WI rate was observed by Mentes et al (5). The other investigators reported different WI rates; 4.5% by Ersoy et al (15), 34% by Akan et al (25), 5% by Dass et al (16), 6.6% by Altintoprak et al (19), and 13% by Cetin et al (24). WI rate was 5.4% in our MLF group.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Using MLF technique, 0.8% WI rate was observed by Mentes et al (5). The other investigators reported different WI rates; 4.5% by Ersoy et al (15), 34% by Akan et al (25), 5% by Dass et al (16), 6.6% by Altintoprak et al (19), and 13% by Cetin et al (24). WI rate was 5.4% in our MLF group.…”
Section: Discussionmentioning
confidence: 40%
“…In addition, we could not correlate the EC development with TDR in both groups (Table 2). Cetin et al showed the average TDR was 4.4 ± 1.5 days in patients of LF group with mattress sutures (24).…”
Section: Discussionmentioning
confidence: 96%
“…Through the summary of the previous related literature, we found that the causes of the above incisional healing defects are as follows: (I) minimally invasive surgery, especially uniportal surgery, increased the chance of burns, postoperative aseptic necrosis, fat liquefaction and can lead to incision healing delay because of the surgical incision of blood leakage, especially during the deep muscle hemostasis. (II) The increase in the number of surgical instruments inserted through the single-hole causes pressure and friction on the incision tissue, resulting in local ischemic necrosis and affecting wound healing ( 17 ). (III) The retention of chest tubes can affect incision healing.…”
Section: Discussionmentioning
confidence: 99%
“…Closed methods involve excision with primary closure to the midline or lateral suture line. Several closed methods of excision and suturing techniques have been described for surgical treatment of PS [34567]. In the last 5–10 years, minimally-invasive procedures, such as endoscopic methods, laser therapy, microsinusectomy, and pit-picking, have been described for the treatment of PS, with evidence of short-term positive results[58910111213].…”
Section: Introductionmentioning
confidence: 99%